2020
DOI: 10.1002/anie.202008166
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Cyclopentadienyl Ligands: Design, Syntheses, and Applications in Asymmetric Catalysis

Abstract: The creation of new chiral ligands capable of providing high stereocontrol in metal-catalyzed reactions is crucial in modern organic synthesis.The production of bioactive molecules as single enantiomers is increasingly required, and asymmetric catalysis with metal complexes constitutes one of the most efficient synthetic strategies to access optically active compounds.H erein we offer ah istorical overview on the development of chiral derivatives of the ubiquitous cyclopentadienyl ligand (Cp X ), and detail th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(97 citation statements)
references
References 189 publications
0
96
0
1
Order By: Relevance
“…Chiral transition-metal cyclopentadienyl (Cp x ) complexes have emerged as powerful stereodirecting catalysts in enantioselective C-H functionalization transformations, 12 and a variety of chiral Cp x complexes have been synthesized and successfully applied in asymmetric reactions. 13,14 In 2017, Rovis et al reported the diastereoselective benzamidation of cyclopropenes with aryl hydroxamates using a bulky nonchiral Rh(III)-indene complex.…”
Section: Feature Synthesismentioning
confidence: 99%
“…Chiral transition-metal cyclopentadienyl (Cp x ) complexes have emerged as powerful stereodirecting catalysts in enantioselective C-H functionalization transformations, 12 and a variety of chiral Cp x complexes have been synthesized and successfully applied in asymmetric reactions. 13,14 In 2017, Rovis et al reported the diastereoselective benzamidation of cyclopropenes with aryl hydroxamates using a bulky nonchiral Rh(III)-indene complex.…”
Section: Feature Synthesismentioning
confidence: 99%
“…Notably, Group 9 cyclopentadienylmetal (CpM III , M=Co, Rh and Ir)‐catalyzed asymmetric C−H activation [2] has achieved great success by using chiral Cp ligands, [3] artificial metalloenzymes, [4] achiral CpM in combination with chiral carboxylic acids or chiral sulfonates, [5] or chiral transient directing groups [6] . So far, the use of CpM catalysts derived from chiral Cp ligands has become one of the most general and effective methods to realize asymmetric C−H activation [3a] . Since the pioneering work by Cramer, [7] diverse chiral Cp ligands have been revealed, including cyclohexane‐fused Cp I , [7–8] binaphthyl Cp II , [9, 10] spirobiindanyl Cp III , [11, 12] biphenyl Cp IV , [13] piperidine‐fused Cp V , [14, 15] cyclopentane‐fused Cp VI , [16] and ferrocenyl Cp VII [17] (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…Rhodium catalysts with chiral cyclopentadienyl ligands have recently attracted a lot of attention thanks to their successful application in C-H activation reactions. [1][2][3][4][5][6] The most explored catalysts of this type are the binaphthyl derivatives 1 developed by Cramer et al and You et al, [7][8][9][10][11] the amino acid derivatives 2 developed by Antonchik and Waldmann et al, [12] the streptavidine-docked derivatives 3 developed by Ward and Rovis et al, [13,14] as well as some others [15][16][17][18][19][20] (Scheme 1). A wide application of these catalysts is still somewhat limited by their multistep synthesis involving rather expensive starting materials and reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodium catalysts with chiral cyclopentadienyl ligands have recently attracted a lot of attention thanks to their successful application in C–H activation reactions . The most explored catalysts of this type are the binaphthyl derivatives 1 developed by Cramer et al and You et al, the amino acid derivatives 2 developed by Antonchik and Waldmann et al, the streptavidine‐docked derivatives 3 developed by Ward and Rovis et al,, as well as some others (Scheme ).…”
Section: Introductionmentioning
confidence: 99%